Tragedy and History: Approaches for an Ethics of Action - Chataignier, Gustavo (2025)
The aim of this paper is to propose, through a study of tragedy, an ethical reconfiguration of communal life that enables us to move beyond the typical modern dichotomies, notably the division between subject and object. Rendering the tragic process explicit necessarily leads to a shared, affective, and unplanned point with the aim of reformulating the very rationality of the unilateral history determined under a normative field. Following the conceptual developments, I intend to establish a connection between the themes of tragedy and history in Hegel from the perspective of a theory of action.